STUDY OF THE KINETIC ONE COAGULATION OF THE COLOIDAL SYSTEM OF Fe(OH)3 BY INFLUENCE OF SODIUM ALGINATE - Rojas P., Nora (2009)
lt has been studied the influence of the concentration and the pH of solution of sodium alginate in the kinetic of coagulation of colloidal system of Fe(OH)3 with positive colloidal particles. From the experimental date we deduce that coagulation is better for 0.1% of concentration and pH=4.